Regioselective peri-C–H selenylation of aromatic compounds with weakly coordinating ketone groups. Issue 82 (27th September 2022) - Duan, Bingbing; Wu, Yao; Gao, Yi; Ying, Linkun; Tang, Jielin; Hu, Shiyu; Zhao, Qiuhua; Song, Zengqiang
Abstract : The first method for the preparation of 5-selenyl chromones has been developed via regioselective selenation of chromones with diselenides under Ru(ii ) catalysis, this protocol is also applicable for other (hetero)arenes bearing ketone groups. Abstract : A novel and versatile method for peri -C–H selenylation of aromatic compounds bearing ketone groups, including chromones, xanthones, acridinones, quinolinones and naphthoquinones with diselenides under Ru(ii ) catalysis is presented. Various chromones and diselenides are applicable for this transformation, affording 5-selenyl chromones in a highly regioselective manner in good to excellent yields. This transformation is easy to scale up and the desired products can be further modified. Most importantly, this transformation allows the late-stage selenylation of bioactive compounds. Mechanistic studies show that radicals may be involved in this novel transformation.